Benign Infantile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The clinical features of 58 patients with benign infantile convulsions (BIC), seen at the Department of Pediatrics, University of Bologna, Italy, over a 20 year-period (1983-2003), are reviewed retrospectively, with reference to both familial and nonfamilial cases.